2016
DOI: 10.1007/s12119-016-9335-4
|View full text |Cite
|
Sign up to set email alerts
|

Law and LGBQ-Parent Families

Abstract: This paper addresses how the law affects LGBQ-parent families. We first outline the legal landscape that LGBQ parents face in the US, underscoring that it varies drastically by state and creates inequity for families. Reviewing existing social science research, we then address how the law affects three processes for LGBQ people: desiring parenthood, becoming a parent, and experiencing parenthood. Our review indicates that the law affects if and how LGBQ people become parents.LGBQ people consider the law as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…Providing accurate legal information and assistance for LGBQ people interested in adopting may be particularly important. Some LGBQ people are more open to adoption and have more expansive understandings of family and parenthood than do their heterosexual peers (Goldberg et al, ; Kazyak et al, ). Yet research indicates the need for all LGBQ prospective parents, regardless of pathway chosen, to have adequate legal information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Providing accurate legal information and assistance for LGBQ people interested in adopting may be particularly important. Some LGBQ people are more open to adoption and have more expansive understandings of family and parenthood than do their heterosexual peers (Goldberg et al, ; Kazyak et al, ). Yet research indicates the need for all LGBQ prospective parents, regardless of pathway chosen, to have adequate legal information.…”
Section: Discussionmentioning
confidence: 99%
“…Second, social science research also indicates that LGBQ people have perceived certain pathways to parenting as more legally secure than others. Specifically, many LGBQ people view donor insemination and surrogacy as the most legally secure pathways to parenthood (Baumle & Compton, ; Berkowitz, ; Lev, ; Park, Kazyak, & Slauson‐Blevins, ; Ryan & Berkowitz, ). Ryan and Berkowitz (), for instance, found that many lesbian women viewed donor insemination as more secure from a legal perspective than other pathways to parenthood, given that the birth mother would automatically be recognized as a parent on the birth certificate.…”
Section: Social Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, sexual minorities’ desires for pursuing parenthood are shaped by their perceptions of access, social support, as well as contextual constraints related to the workplace, legal structures and healthcare systems (Gato et al., 2017; Kazyak & Woodell, 2016; Riskind & Patterson, 2010). For LGB young people in particular, however, parenthood aspirations are also uniquely impacted by their formative developmental trajectories that can include processes of identity development and the emergence into adulthood.…”
Section: Literature Reviewmentioning
confidence: 99%